Gyrostat Dynamics on a Circular Orbit: General Case of Equilibria Bifurcation and Analytical Expressions - Santos, Luís (2019)
This paper is on the study of the Dynamics of a Gyrostat Satellite on a Circular Orbit, and the achievement of the analytical expressions which describes the bifurcation of equilibria. The attitude control of modern spacecraft's is essential to fulfil its missions. Every time that is necessary to point a camera or a scientific instrument the space platform must be perfectly balanced and stabilized. When a space platform loses its ability to be balanced and stabilized, which might be due to several factors, loses also its ability to carry out its mission. One approach to achieve such conditions is using Gyrostat configuration.